Going Beyond the Catch-22 of Autism Diagnosis and Research. The Moral Implications of (Not) Asking “What Is Autism?” - Bervoets, Jo; Hens, Kristien (Frontiers in Psychology, 2020)
Psychiatric diagnoses like Autism Spectrum Disorder (ASD) are primarily based on purely behavioral criteria. The aim of most of the biomedical research on ASD is to uncover the underlying mechanisms that lead to or even cause pathological behavior. However, in the philosophical and sociological literature, it has been suggested that autism is also to some extent a ‘social construct’ that cannot merely be reduced to its biological explanation. We show that a one-sided adherence to either a biological or a social explanation leads to a moral dilemma, a Catch-22, for autistics and for those living with them. Such explanations close the space for self-identifying as autistic and at the same time being considered to be in good mental health. They foreclose the possibility of making sense of the lived experience of (and with) autistics. In this paper we argue that a lack of space for moral imagination inherently leads to scientific stalemate. We propose that one can only go beyond this stalemate by taking an ethical stance in theorizing, one that enables better intersubjective understanding. Only on such a view can behavior and nature be linked without either disconnecting them or reducing the one to the other.